Ethnomathematics Exploration on Typical Angkola Woven Patterns, Sipirok, South Tapanuli, North Sumatra, Indonesia - Hakim Fahrezi; Siti Salamah Br Ginting (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2023)
This research explores the application of mathematical elements found in certain cultures. The object that is the focus of this research is the woven fabric typical of the Angkola ethnic group, which is part of the cultural heritage of the Angkola tribe in South Tapanuli district, North Sumatra province. Descriptive qualitative is the research model used in this study and ethnography is the research approach used, focusing on ethnomathematics in the motifs of Angkola's typical woven fabrics. The summary result of the research is that there is an application of mathematical concepts in this cultural heritage object, namely the basic concept of flat geometric shapes, the applied concept of geometric transformation, and the concept of sets. With this research it is hoped that it can contribute to new ethnomathematics research references and can be used as a reference for new mathematical category learning approaches, especially for the province of North Sumatra.